The current state of Belarusian-Israeli relations: basic trends - Shykh, K.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
The article is devoted to the cooperation between the Republic of Belarus and the State of Israel at the present stage. This article describes the main factors that influence to the foreign policy of the two states, priority directions of the foreign policy of Belarus and Israel, and tools for its implementation. The basic cooperation forms between two countries are stated in the article. The author points out the lack of comprehensive studies of this issue by Israeli authors and considers that it demands further research. This article discusses the main areas of the Belarusian-Israeli cooperation at the new stage as well as its challenges and prospects. The author systematizes information related to the interaction between the two countries in various fields. He talks about the forms and types of activity of the two States. The article gives a brief description of the present stage of political dialogue and economic relations between the two countries. The article not only discusses current trends and features of political dialogue between Belarus and Israel, but also researches the regulatory framework that ensures effective regulation of economic relations between these States. The direct participation of Belarus and Israel in the cooperation is analyzed by examples of networking. Separate attention is paid to the analysis of the closure of the Israeli embassy in Minsk. The article sumps up some results of studying of this problem within recent years.